asked on # Maths question

I have a algebra question, the below problem already has the answer (4 & -2) but I need to know the x & y value AND the x and the y on both need to be the same value.. help lol

3x + 8y = 4

3x + 2y = -2

3x + 8y = 4

3x + 2y = -2

Math / Science

Thanks ozo!!

However, I probably didnt word it right

3x + 8y = 4

3x + 2y = -2

the x and both lines need to be the same value as does the y to get the answer... make sense?

However, I probably didnt word it right

3x + 8y = 4

3x + 2y = -2

the x and both lines need to be the same value as does the y to get the answer... make sense?

The 2 x values and the 2 y values must be the same but the x and the y could be different. So one way to solve this would be to take one of the equations and get it so one letter is on a side by itself.

3x+8y=4

8y=4-3x

y = (4-3x)/8

Now since you know what y is you can plug that into the second line.

From 3x+2y=-2 you get

3x+2*[(4-3x)/8]=-2

Then you can solve this algebraically to find that x is -4/3.

Now you can take that and plug it back into either one of the equations to be able to solve for y.

3x+8y=4

8y=4-3x

y = (4-3x)/8

Now since you know what y is you can plug that into the second line.

From 3x+2y=-2 you get

3x+2*[(4-3x)/8]=-2

Then you can solve this algebraically to find that x is -4/3.

Now you can take that and plug it back into either one of the equations to be able to solve for y.

3x + 8y = 4

so: 3x = 4 -8y

3x + 2y = -2

so: 3x = -2 -2y

therefore:

4 - 8y = -2 -2y

so: 6 = 6y

so: y=1

therefore: 3x = -2 -2

so: 3x = -4

so: x = -4/3

RESULT: x=-4/3 and y=1

so: 3x = 4 -8y

3x + 2y = -2

so: 3x = -2 -2y

therefore:

4 - 8y = -2 -2y

so: 6 = 6y

so: y=1

therefore: 3x = -2 -2

so: 3x = -4

so: x = -4/3

RESULT: x=-4/3 and y=1

View this solution by signing up for a free trial.

Members can start a 7-Day free trial and enjoy unlimited access to the platform.

I'm confused by the accepted solution. That wasn't an answer to your question!

I guess the intended question wasn't the question some of us thought it was.

3x + 2y = -2

(3x-3x) + (8y-2y) = (4 - -2)